1991
DOI: 10.1161/01.str.22.12.1554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenergic drugs on cerebral blood flow, metabolism, and evoked potentials after delayed cardiopulmonary resuscitation in dogs.

Abstract: Background and Purpose: Epinephrine administration during cardiopulmonary resuscitation increases cerebral blood flow by increasing arterial pressure. We tested whether potential /3-adrenergic effects of epinephrine directly influence cerebral blood flow and oxygen consumption independently of raising perfusion pressure.Methods: Four groups of seven anesthetized dogs were subjected to 8 minutes of fibrillatory arrest followed by 6 minutes of chest compression, ventricular defibrillation, and 4 hours of spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The dose of epinephrine chosen in this study has been shown to improve myocardial and cerebral blood flow during CPR in immature piglets (18,30). In addition, epinephrine does not appear to have central effects that might improve SEP independent of improving cerebral blood flow (20,31). Cerebral edema is usually described as either cytotoxic or vasogenic to refer to two different mechanisms.…”
Section: P1 Asphyxiamentioning
confidence: 99%
“…The dose of epinephrine chosen in this study has been shown to improve myocardial and cerebral blood flow during CPR in immature piglets (18,30). In addition, epinephrine does not appear to have central effects that might improve SEP independent of improving cerebral blood flow (20,31). Cerebral edema is usually described as either cytotoxic or vasogenic to refer to two different mechanisms.…”
Section: P1 Asphyxiamentioning
confidence: 99%
“…Fourth, epinephrine was not used during the experiment. Epinephrine is known to elevate CoPP and have a temporary cerebral vasoconstriction effect [41]. Epinephrine was not used to minimize its effect on EEG.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pichler et al [18] found that rSrO 2 may underestimate kidney hypoxia in newborn piglets, our results indicate that rSrO 2 is a more sensitive marker of detrimental hypoxic organ injury than rScO 2 . Gervais et al [19] demonstrated in dogs with ventricular fibrillation that brain and heart blood flow were better preserved during CPR than that of, for example, the kidney. After resuscitation, the kidney blood flow remained depressed, whereas blood flow to the other organs recovered.…”
Section: Discussionmentioning
confidence: 99%